Simplified E-Content system (SECS) - Oon, Seau Foong (2014)
This project entitled "Simplified E-Content System (SECS) which is a system created to help entrepreneurs who are "normal user" with less literacy in web technology and ICT who want to have their website to promote their products. Content Management System (CMS) in the market is good to use but it require a lot of steps to create some content thus making it hard for normal user. With this system, they only need to fill in information step by step inside this system and this system will help them to generate a website for them to promote their products. This system is focus on entrepreneurs who are "normal user" with less literacy in web technology and ICT. For the development process, Waterfall is chosen to be used in this project. Programming Hypertext Preprocessor (PHP), Cascading Style Sheet (CSS), JavaScript, Hypertext Markup Language (HTML), and MySQL are used to develop this system as the web programming language and database management respectively.